Renegotiating Access to Shea Trees in Burkina Faso: Challenging Power Relationships Associated with Demographic Shifts and Globalized Trade - Rousseau, K.; Gautier, D.; Wardell, D.A. (Wiley, 2017)
This paper uses an original integrated theoretical framework to reveal the mechanisms behind socio‐economic differentiation in the changing patterns of access to shea in western Burkina Faso, in the context of globalization of the shea nut trade and internal migrations from both the Mossi Plateau and the Sahelian zone. Based on more than 200 interviews, we unravel the complex dynamic mechanisms of changes in access to shea. We show that negotiations result in reduced access to shea for late comers as well as for people with a limited number of shea trees in their fields, since areas where shea is managed as a common‐pool resource are becoming less accessible. However, we also demonstrate that late comers are not powerless in the face of first comers’ claims to shea. Our results should help policy‐makers and project‐based activities concerning shea to focus more on issues related to access to this resource.